Hegel’s Theory of Time - Gentry Gerad (Open Philosophy)
While sharing some features in common with presentist accounts of time, Hegel’s theory of time fundamentally offers an alternative to standard A-Theories, B-Theories, and C-Theories of time. While compatible with Kantian ideality of time on the one hand and spacetime in the theory of general relativity on the other, Hegel’s theory of time reaches beyond both a transcendental form of sensibility on the one hand and a paradigm for material motion in physics, on the other. Further, while Hegel’s theory of time provides reason to reject such theories of time as the Moving Spotlight, Growing and Shrinking Block, and a range of others, my interest here is in making comprehensible Hegel’s theory of time itself. I will argue that according to Hegel’s theory, the past and the future exist as constitutive of the now, and the now is not separable from space, but rather is itself spatial becoming. Stemming from his underlying logic of actuality and becoming, Hegel espouses the view that history (the past) and future possibility are present and constitutive of the “now.” Understanding his theory of time will also help shed some light on a systematic feature found across his philosophy of nature and mind. Additionally, while his theory presents an elegant notion of time within his philosophy, it also offers an intuitive and productive solution for a traditional identity problem of concrete particulars across time and intervenes in contemporary philosophy of time.